Integration of Educational Technology and Artificial Intelligence - Daniel Robert Wong; Budi Santoso Wijaya (Innovate Inovation Teaching And Learning, 2025)
This study aims to explore the integration of educational technology and artificial intelligence in improving the quality of learning in the digital era, with a focus on pedagogical effectiveness, user experience, and systemic implications. Using a mixed-methods approach with a sequential explanatory design, the study involved 450 respondents from 25 educational institutions in Indonesia. The results showed that AI-based learning improved academic outcomes by 23.4% with a significant personalization effect for low-ability students (37.8%). Intelligent tutoring systems and learning analytics have proven effective in providing formative feedback and early identification of at-risk students. However, implementation faces infrastructure challenges, the digital divide, and ethical issues related to data privacy and algorithmic bias. Transforming the role of educators from transmitters to facilitators requires comprehensive professional development and organizational support. This study recommends a holistic approach that integrates technological, pedagogical, and ethical aspects in the implementation of educational AI to ensure accessibility, effectiveness, and equity for all learners.